Level of Understanding of ECE Teachers and Elementary School Teachers in the Implementation of ECE-ES Transition in Bekasi City - El Liza, Mona; Puridawaty, Brigita (Kirana Publisher (KNPub), 2025)
Through research on the level of understanding of ECE teachers and elementary school teachers in implementing the ECE-SD transition, researchers hope to be able to help. bridging and harmonizing​​ learning Preschool – Elementary School . In the implementation of the ECE - SD Transition, the most important thing is the level of understanding of ECE teachers and SD teachers in its implementation in ECE and SD units, which is often hampered by the absence of the same perception and collaboration between ECE teachers and SD teachers, as well as the absence of the same perception between ECE and SD units in implementing the ECE - SD transition. The purpose of this study was to see the level of understanding of ECE teachers and SD teachers in implementing the ECE - SD transition in the city of Bekasi. The researcher used a descriptive method quantitative with spread questionnaire to Teacher Early Childhood Education And Teacher SD in city Bekasi. With a sample of 70 teachers , the results obtained were that level of understanding of ECE teachers and elementary school teachers about the ECE – SD transition in the city Bekasi is at on category